Curing over-use by prescribing fees: an evaluation of the effect of user fees' implementation on healthcare use in the Czech Republic - Kalousova, Lucie (Health policy and planning, 2015)
In 2008, the Czech Republic instituted a new policy that requires most patients to pay a small fee for some inpatient and outpatient healthcare services. Using the Survey of Health Aging and Retirement in Europe, this article examines the changes in healthcare utilization of Czechs 50 years and older following the new fee requirement by constructing difference-in-differences regression models focusing on four outcome measures: any visits to primary care physician, any hospitalization, number of visits to the primary care physician and number of nights hospitalized. For this population, I find that the likelihood of having any primary care visit decreased after the policy was instituted. The likelihood of reporting any hospitalization was not significantly changed. The predicted number of primary care visits per person declined, but the predicted number of nights spent in a hospital did not. I find only mixed evidence of greater effect of the user fees on some subpopulations compared with others. Those 65 or older reduced their use more than those between 50 and 64, and so did those who consider their health to be good, and the less educated.
Keywords: Health Surveys; lidé; Middle Aged; primární zdravotní péče; primary care; pacientův souhlas se zdravotní péčí; Primary Health Care; access; Longitudinal Studies; Humans; Health Services Accessibility; User fee; Česká republika; inequality; lidé středního věku; dostupnost zdravotnických služeb; Czech Republic; zdravotnické přehledy; Fee-for-Service Plans; platba za výkon; longitudinální studie; Aged; Patient Acceptance of Health Care; senioři